1982
DOI: 10.1111/j.1471-4159.1982.tb12534.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Depolarization‐Induced Release of γ‐Aminobutyric Acid from Brain Slices by Antibodies to Ganglioside

Abstract: The effect of antibodies to GM1 ganglioside on release of neurotransmitters from rat brain slices was studied. Depolarization-induced (40 mM-KCl or veratrine) release of gamma-aminobutyric acid was markedly enhanced. Depolarization-induced release of norepinephrine was only slightly enhanced, whereas that of serotonin was unaffected. No effect on spontaneous release was observed for any of these three neurotransmitters. These results show that antibodies that can bind to synaptic membrane antigens may alter ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1982
1982
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…50 Such antibodies have been reported to increase release of neuronal GABA after depolarisation, possibly exerting a convulsant effect by interfering with kindling51 or inhibiting the interaction of GABA with synaptic receptors and/or transport sites 52. Anti-GM1 antibodies in peripheral neuropathies are thought to interfere with conduction by their action on voltage gated Na + and possibly K + channels of myelinated nerve fibres53; however, this mechanism of action has not been investigated in the CNS.…”
Section: Antibodies Associated With Unselected Patients With Epilepsymentioning
confidence: 99%
“…50 Such antibodies have been reported to increase release of neuronal GABA after depolarisation, possibly exerting a convulsant effect by interfering with kindling51 or inhibiting the interaction of GABA with synaptic receptors and/or transport sites 52. Anti-GM1 antibodies in peripheral neuropathies are thought to interfere with conduction by their action on voltage gated Na + and possibly K + channels of myelinated nerve fibres53; however, this mechanism of action has not been investigated in the CNS.…”
Section: Antibodies Associated With Unselected Patients With Epilepsymentioning
confidence: 99%
“…Subsequently GM1 ganglioside was found to be the receptor molecule for the cholera toxin [King and van Heyningen, 1973;Cuatrecasas, 1973;Staerk et al, 19741. It has been suggested that gangliosides play roles in synatpic transmission and memory generation, stimulate axonal outgrowth in culture, and promote axonal regeneration in vivo [Gorio et al, 1980;Frieder and Rapport, 1981;Morgan and Seifert, 1979;Roisen et al, 198 1 ;Ledeen et al, 19841. It is generally believed that most brain cell types contain similar patterns of ganglioside species [Hamberger and Svennerholm, 1971 ;Abe and Norton, 1974;Norton et al, 19751. There are, however, some disagreements concerning this view; the existence of differences in ganglioside distribution between various brain regions has been known [Suzuki, 1965;Seyfried et al, 1978;19821, as has the exclusive localization of GM4 ganglioside in myelin and oligodendrocytes isolated from human brains [Ledeen et al, 1973;Yu and Iqbal, 19791.…”
Section: Introductionmentioning
confidence: 98%
“…However, when monospecific antibodies to these antigens are obtained, they should be useful in providing additional evi-dence for synaptic localization by immunocytochemical techniques. Further, since antibodies to synaptic membrane constituents can affect synaptic functions such as uptake and release of neurotransmitters (Haglid et al, 1979;Hofstein et al, 1981;Frieder and Rapport, 1981) and behavioral performance (Rapport et al, 1978), the antibodies can be used t o relate antigenic structures to neurobiological processes, and thus attack the problem of functional assignment.…”
Section: Discussionmentioning
confidence: 99%